(untitled) (Research, Society and Development, 2023)
Schizophrenia is a chronic, multifactorial condition prevalent in 1% of the global population. Treatment is carried out with conventional or atypical antipsychotics. The evolution in the treatment of schizophrenia has occurred with atypical antipsychotics, as they offer fewer side effects and allow for simultaneous action on both the positive and negative symptoms of the disease. These drugs are used for the control of schizophrenia as well as other psychopathologies, for example, Bipolar Affective Disorder (ICD-10 F31). The labels of antipsychotic medications warn against the use of the medication in diabetic patients or those at risk of developing diabetes, recommending glycemic monitoring for such patients. As a result of this effect, the present study aims to gather information about the development of diabetes due to the use of atypical antipsychotics for the treatment of schizophrenia, schizotypal disorders, delusional disorders, and other disorders resembling schizophrenia. This is a descriptive research with quantitative analysis, focusing on bibliographic data and field research, in which data were collected through medical records of patients in the coverage area of the Psychosocial Care Center (CAPS II) in the city of Maringá, PR. The results found through this study include the side effects of the medications, their relationship with age, gender, dosage, and duration of use. Furthermore, the multifactorial influence on the development of other comorbidities can be observed. This can contribute to providing proper guidance, emphasizing the harm that the improper administration of these medications can cause.